Harmonisasi Hubungan dengan Alam Melalui Perjanjian Kekal Allah dengan Makhluk Hidup Berdasarkan Kejadian 9:12-17 - Pakpahan, Abraham Gerald (Sekolah Tinggi Teologi Berita Hidup, 2024)
In showing the relationship between humans and nature, interpreters still often use Genesis 1:28 to understand humans' relationship with the rest of creation. The words 'conquer' and 'dominate' in caring for the earth are interpreted as the superior power possessed by humans to view the relationship between humans and nature because Allah gave them the responsibility and right to regulate and rule all creation on earth. This interpretation gives rise to power that is hierarchical in nature because humans are placed directly above other created creatures so that humans can exploit created creatures according to human wishes. Through Genesis 9:12-17, researchers will conduct research to see the eternal covenant that God made to humans and all other creations. God's eternal covenant with living creatures is the basis for seeing God's attitude towards all of His creatures. Is the anthropocentric attitude still the basis on which humans view the rest of God's creation? So, this research can become one of the foundations of ecological theology, which is able to change the attitude of viewing other created creatures only as beneficial interests for humans to viewing created creatures from their intrinsic value. Other created creatures cannot be manipulated by humans, so it is not the nature of exploitation that is born but the nature that loves created creatures.